ACONITATE DECARBOXYLASE 1 IS A KEY REGULATOR OF COLITIS. (26th January 2023) - McNamara, Kara; Latour, Yvonne; Smith, Thaddeus; Barry, Daniel; Allaman, Margaret; Delgado, Alberto; Piazuelo, M Blanca; Washington, Mary; Zhao, Shilin; Coburn, Lori; Gobert, Alain; Wilson, Keith
Abstract: INTRODUCTION: Aconitate decarboxylase 1 (ACOD1; also known as IRG1) is highly expressed in activated macrophages and converts cis -aconitate to itaconate, which contributes to the antimicrobial activity of macrophages. The role of ACOD1 in intestinal inflammation remains unknown. Therefore, we investigated the role of ACOD1 during colitis induced by Citrobacter rodentium ( C. rodentium ), a murine bacterial pathogen used to model the pathogenesis of enteropathogenic Escherichia coli, and dextran sulfate sodium (DSS) a model of epithelial injury-mediated inflammation. METHODS: The GEO database was utilized to examine ACOD1 mRNA levels in ulcerative colitis (UC) and Crohn's disease (CD) patients, and normal controls. C57BL/6 wild-type (WT) and Acod1 –/– mice were infected with C. rodentium for 14 days or given 4% DSS for 5 days and then normal drinking water for 5 days. Mice were weighed daily. Histology was analyzed by H&E staining on colon Swiss rolls using a 0-21 scale for C. rodentium infection and a 0-40 scale for DSS. DNA was extracted from stool to use for 16S microbiome analysis from 5 naïve WT and 5 Acod1 –/– mice. RESULTS: ACOD1 expression is increased in the colon of UC and CD patients compared to normal controls (GEO GSE16879). Further ACOD1 is significantly increased in active UC compared to inactive ( P =0.0256) (GEO GSE75214). C. rodentium -infected Acod1 –/– mice lost significantly more body weight compared to infected WT mice ( P <0.0001). There was a significant increase in histologic injury score in the infected Acod1 –/– mice (12.07 ± 0.93; n =19) compared to infected WT mice (7.65 ± 1.04; n=20; P =0.0087). In the DSS model, we observed a significant decrease in body weight ( P =0.0002) in Acod1 –/– mice compared to controls. A significant decrease in colon length, commonly associated with colitis in mice, was observed in the DSS-treated Acod1 –/– animals (6.07 ± 0.29 cm compared to 7.22 ± 0.32 cm; P =0.0164). This was accompanied by a significant increase in histologic injury score (23.89 ± 2.14) compared to treated WT mice (13.47 ± 2.03; P =0.0004), which was driven by inflammation, epithelial injury, and crypt damage. 16S microbiome analysis on naïve mice from each genotype revealed significant differences in both the phylum and genus. Acod1 –/– mice had significantly more Bacteroidetes ( P =0.03) and Proteobacteria ( P =0.03), specifically more Alloprevotella ( P =0.029) and Prevotellaceae ( P =0.029). CONCLUSION: While ACOD1 is increased in human IBD tissues, our data indicates that this enzyme has a protective role in experimental colitis. Notably, Acod1 deletion is associated with an altered microbiome. Together our findings suggest that enhancement of ACOD1 activity may represent a new therapeutic strategy for IBD.